Peningkatan Hasil Belajar Peserta Didik Melalui Think Pair Share Pada Materi Menulis Puisi Kelas X SMA PGRI 2 Palembang - Supritiani, Febry; Nurma’rifah, Ulva; H, Hetilaniar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The research conducted by the researcher was classroom action research. This research aims to determine the improvement in student learning outcomes through think-pairshare on poetry writing material for class X SMA PGRI 2 Palembang. The data collection techniques used in this research used observation, learning results, and documentation. The steps taken in this research are observation to determine students' initial abilities in the material used, then implementing the Think Pair Share type cooperative learning model with a continuous learning cycle, and ending with exercises at the end of each lesson. The results of the research show that implementing learning using the Think Pair Share type cooperative learning model can improve student learning outcomes in class X 10 poetry writing material at SMA PGRI 2 Palembang. In cycle I the average percentage of student learning outcomes was 58.3%, then in cycle II the average percentage of student learning outcomes was 86.1%, thus the application of the Think Pair Share learning model can be applied to improve student learning outcomes educate students on the material of writing poetry.